2011
DOI: 10.1021/ja2029987
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptic Products of the Gliotoxin Gene Cluster Using NMR-Based Comparative Metabolomics and a Model for Gliotoxin Biosynthesis

Abstract: Gliotoxin (1), a major product of the gli non-ribosomal peptide synthetase (NRPS) gene cluster, is strongly associated with virulence of the opportunistic human pathogen Aspergillus fumigatus. Despite identification of the gli cluster, the pathway of gliotoxin biosynthesis has remained elusive, in part because few potential intermediates have been identified. In addition, previous studies suggest that knowledge of gli-dependent metabolites is incomplete. Here we use differential analysis by 2D NMR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 32 publications
4
88
0
Order By: Relevance
“…These metabolites did not contain free thiols, and as noted above they did not possess growth-inhibitory properties associated with organic extracts of wild-type organic extracts. Also, the observed m/z did not correspond to any metabolite present in the A. fumigatus wild-type intracellular metabolome (13) or secretome of the A. fumigatus ⌬gliG strain (11,31). Moreover, this mass (393 to 395 Da) is greater than that of gliotoxin, 326 Da, and strongly suggests the presence of either a shunt metabolite(s) or biosynthetic intermediate of higher mass than gliotoxin, as previously observed (31).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These metabolites did not contain free thiols, and as noted above they did not possess growth-inhibitory properties associated with organic extracts of wild-type organic extracts. Also, the observed m/z did not correspond to any metabolite present in the A. fumigatus wild-type intracellular metabolome (13) or secretome of the A. fumigatus ⌬gliG strain (11,31). Moreover, this mass (393 to 395 Da) is greater than that of gliotoxin, 326 Da, and strongly suggests the presence of either a shunt metabolite(s) or biosynthetic intermediate of higher mass than gliotoxin, as previously observed (31).…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, this work also demonstrated that gliP and gliI deletion mutant metabolomes did not contain any gliZ-dependent compounds. While this might be expected for GliP absence, which normally catalyzes the initiation step in gliotoxin biosynthesis (1), it is unclear why gliI (a putative aminotransferase) deletion resulted in the complete absence of gliZ-dependent metabolites, although the absence of gliZ and gliP expression in A. fumigatus ⌬gliI has been noted (13).…”
mentioning
confidence: 99%
“…11 Two partial structures (units a and b, Figure 1) were assigned by interpretation of the 2D NMR data (Table 1). In unit a, the connectivity of the three olefinic protons (H-7, H-8, and H-9) was unambiguously assigned from the COSY data.…”
mentioning
confidence: 99%
“…Indeed, existing paradigms of gliotoxin ( Fig. 1) as a toxin and the perspective of the disulfide bridge-containing (oxidized) form as the final, or only, product are undergoing significant reconsideration (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Moreover, multiple S-methylated intermediates have been identified in wild-type A. fumigatus but not in an A. fumigatus strain deficient in gliotoxin biosynthesis (⌬gliZ) (9). Although bisdethiobis(methylthio)gliotoxin (BmGT) (Fig.…”
mentioning
confidence: 99%